Analisis Budaya Kepatuhan Hukum terhadap Penjamin Orang Asing Subjek Universitas pada Wilayah Kerja Kantor Imigrasi Kelas I TPI Padang - Fadhilatul Ikhsan; Koesmoyo Ponco Aji; Tony Mirwanto (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This article analyses the immigration legal culture of foreign students under the sponsorship of universities within the jurisdiction of the Immigration Office Class I TPI Padang. The primary indicator for this analysis is the notably low incidence of immigration violations among this demographic. This study posits that the absence of such violations is not accidental but rather a direct outcome of a well-functioning legal culture, fostered by the university as the sponsor. The objective of this paper is to describe this positive legal culture and the mechanisms that sustain it. Using a normative-empirical method, this research applies Lawrence Friedman's Legal System Theory and H.C. Kelmen's Compliance Theory. The analysis suggests that the legal compliance observed has transcended mere fear of sanctions (compliance) and has evolved towards identification and internalization. Universities have successfully integrated their sponsorship responsibilities into their institutional framework, creating a system that promotes and facilitates legal adherence. The findings indicate that the synergy between legal substance, institutional structure, and a proactive cultural approach by universities has cultivated an environment of high legal awareness and compliance among foreign students.